1953
DOI: 10.1063/1.1698677
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Mobility of Polymers Near Their Glass Temperature

Abstract: Glass forming polymers exhibit a rapid rise of activation energy for molecular motion as T is lowered through the glass temperature. This phenomena is explained here in two different but largely equivalent ways. The first method assumes that in order for a polymer segment to move (i.e., rotate or jump) an energy greater than a critical energy E must be localized on it and its neighbors. The second approach stipulates that a segment may not move unless more than a certain critical amount of free volume is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

1965
1965
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(44 citation statements)
references
References 7 publications
7
37
0
Order By: Relevance
“…Investigating amorphous polymers, Liu et al [21] analysed asymmetrical o-Ps lifetime distributions from which an asymmetrical hole size distribution, correlating well with the free-volume theory of Simha and Somcynsky [22], was estimated. Other authors [23] present more symmetrical o-Ps lifetime distributions, the hole size distributions derived from which agree well with the free-volume theory of Bueche [24], who predicted a Gaussian hole size distribution. Recently, Dai and Jean [18] showed that the asymmetry in analysed distributions is due to the mathematical method used in CONTIN.…”
Section: Introductionsupporting
confidence: 62%
“…Investigating amorphous polymers, Liu et al [21] analysed asymmetrical o-Ps lifetime distributions from which an asymmetrical hole size distribution, correlating well with the free-volume theory of Simha and Somcynsky [22], was estimated. Other authors [23] present more symmetrical o-Ps lifetime distributions, the hole size distributions derived from which agree well with the free-volume theory of Bueche [24], who predicted a Gaussian hole size distribution. Recently, Dai and Jean [18] showed that the asymmetry in analysed distributions is due to the mathematical method used in CONTIN.…”
Section: Introductionsupporting
confidence: 62%
“…Cohen and Turnbull (1959) considered the diffusion of hard spheres in a liquid as the result of a redistribution of the free volume inside the liquid with no energy variation associated. Besides, in 1953, Bueche gave an analysis of the segmental mobility in polymers which was based on the theory of free volume fluctuations (Bueche, 1953;Slater, 1939).…”
Section: Molecular Modelsmentioning
confidence: 99%
“…To compare the relative free-volume fraction deduced from these experimental data to that estimated from a free-volume theory, a theoretical free-volume fraction was calculated from viscosity data according to the Doolittle equation, 46 ln ϭ C 1 ϩ C 2 /f, where is the viscosity and C 1 (ln 0 ) and C 2 are constants. ln is plotted versus a reciprocal relative free-volume fraction, 1/f s , and is shown in Figure 4 Buchue 47 and Fox and Flory 48 suggested that the temperature dependence of the free-volume fraction for a polymer system is the difference between the thermal expansion coefficient above and below the glass-transition temperature, T g , as shown below:…”
Section: Variation Of the Free Volume Of An Acetone-water Mixed Solvementioning
confidence: 99%